Emergency Nurses’ Perception of Patient Safety Culture at King Saud Medical City - Sarah Alqahtani, Mohammad AlKhatib, Sami alqasem, Jamilah alqhtani, Edah Alonizi, Razan Alrwashed, Razan Faqihi, (Journal of International Crisis and Risk Communication Research, 2024)
This research explores the perception of patient protection culture among emergency nurses at King Saud Medical City. The study examines key dimensions of safety culture, including teamwork, communication, error reporting, and leadership support. Utilizing a descriptive and analytical approach, data were collected via the Hospital Survey on Patient Safety Culture (HSOPSC), involving 210 nurses across pediatric, maternity, and general emergency departments. Findings indicate that 46.7% of nurses rated the safety culture as “acceptable,” with 40% assessing it as “very good.” Critical strengths include teamwork within units (74%) and leadership acknowledgment of safety adherence (76.67%). However, challenges persist, such as inadequate staffing levels (65.33%) and fear of punitive repercussions for errors (76%), which hinder open reporting. Additionally, communication breakdowns between hospital units (76.67%) were identified as a major issue. Demographic analysis revealed that younger nurses and expatriates face unique challenges, including lower perceptions of communication effectiveness. The research underscores the importance of fostering a non-punitive culture, improving interdepartmental communication, and implementing structured safety protocols. The study concludes that while a foundational understanding of safety culture exists, targeted interventions are needed to enhance communication, leadership engagement, and error reporting. These findings offer actionable insights for healthcare administrators to strengthen patient safety and improve the overall quality of care in emergency settings